1986
DOI: 10.1152/jappl.1986.60.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Formyl peptide-induced contraction of human airways in vitro

Abstract: Formylmethionylleucylphenylalanine (FMLP) is a synthetic analogue of bacterial chemotactic factors. We studied the contraction of human airway tissue in vitro by FMLP. FMLP induced a concentration-dependent contraction of all bronchial spiral strips studied (n = 45). The maximum tension generated in response to FMLP was 86.6 +/- 7.0% (SE) of the maximum response to histamine. The contraction was not reduced by the histamine H1-receptor antagonist pyrilamine, the cyclooxygenase and lipoxygenase inhibitors indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…Fpr1 is expressed in leukocytes (30), and is thought to modulate bronchoconstriction indirectly through the action of metabolites of arachidonic acid in guinea pigs and humans (31,32). Previous reports documented the expression of Fpr1 in human bronchial ASM and in numerous other tissues (33), but we did not detect it in murine ASM using immunohistochemistry, arguing for an indirect role in the contraction of ASM.…”
Section: Discussioncontrasting
confidence: 72%
“…Fpr1 is expressed in leukocytes (30), and is thought to modulate bronchoconstriction indirectly through the action of metabolites of arachidonic acid in guinea pigs and humans (31,32). Previous reports documented the expression of Fpr1 in human bronchial ASM and in numerous other tissues (33), but we did not detect it in murine ASM using immunohistochemistry, arguing for an indirect role in the contraction of ASM.…”
Section: Discussioncontrasting
confidence: 72%
“…An alternate mechanism for the bronchoconstriction effect of FMLP is a direct effect on a smooth muscle receptor. The previous reports on the effects of FMLP on guinea pig smooth muscle in vitro [13] and a recent report in which human airway smooth muscle contracted in response to FMLP [15] are in keeping with this notion. However, the fact that FMLP failed to elicit contraction of rabbit airway smooth muscle in vitro in the present study suggests that the bronchoconstriction is not mediated by a smooth muscle receptor.…”
Section: Discussionsupporting
confidence: 63%
“…Recent reports [13,14] suggest that FMLP causes contraction of guinea pig and human [15] airway smooth muscle. It has been shown that neutrophil infiltration into the airway wall, whether induced by exposure to ozone or chemotactic complement components, is associated with increased airway responsiveness to acetylcholine [18,19] and histamine [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetie baeterial chemotaetie factor formyl-methionyl-leucylphenylalanine (FMLP) also aetivates neutrophils [7]. In addition it has been shown to cause bronchoconstriction in vitro [8] and in vivo [9]. Human neutrophils primed with GM-CSF and then stimulated with FMLP produee detectable amounts of the leucocyte chemotactic factor leukotriene B4 [10].…”
Section: Introductionmentioning
confidence: 99%